VALUE IN PROCESSING SYSTEMS MANAGEMENT ACADEMY DEVELOPMENT TOOLS INFORMATICS AND COMPUTER INFORMATION (AMIK-BSI) - Mulya Rahmatullah; Ir. Susi Wagiyati, MM Ir. Susi Wagiyati, MM (Jurnal Sistem Informasi, 1998)
The implementation of processing systems that value when ni walk, this maximumhas not been assessed because of the department concerned has not been connected.So that system integrity is not prominent, consequently if there are parts that will beaccessing the data at the same time there are other parts also access a data at the sametime there are other parts which are also access data tersenut, probably not producethe same output would be greater.